The pragmatics of interaction - D'hondt, Sigurd; Östman, Jan-Ola; Verschueren, Jef (Handbook of pragmatics highlights ;, 2009)
The ten volumes of Handbook of Pragmatics Highlights focus on the most salient topics in the field of pragmatics, thus dividing its wide interdisciplinary spectrum in a transparent and manageable way. While the other volumes select specific philosophical, cognitive, grammatical, social, cultural, variational, or discursive angles, this fourth volume is dedicated to the empirical investigation of the way human beings organize their interaction in natural environments and how they use talk for accomplishing actions and their contexts. Starting from Goffman's observation that interaction exhibits.